The Influence Of JASA TAMI (Healthy Adolescents Without Anemia) Booklet Media On Adolescent Girls In Islamic Boarding Schools Mizanul ‘Ulum Sanrobone In 2023 - M, Fifiana Agustianingsih; Rahma, Nur Rahmawati Sholihah; Rahayu, Budi (JURNAL KEBIDANAN KESTRA (JKK), 2024)
Background: Anemia is a health problem that often occurs in adolescent girls. Anemia is a condition in which the number and size of erythrocytes or hemoglobin concentration is below the threshold value and results in a decrease in the overall blood transport capacity of the body. The prevalence of adolescent anemia ranges from 40-80%. According to WHO, the incidence of anemia in adolescent girls in developing countries is about 53.7% of all adolescent girls. Objective: To determine the influence of the JASA TAMI (Healthy Adolescents Without Anemia) booklet media on the knowledge and attitudes of anemia prevention for adolescent girls at the Mizanul 'Ulum Sanrobone Islamic Boarding School in 2023. Method: The researcher used pre-experiment method with one group pretest-posttest design. The research time is on May 22-May 27, 2023 with 32 respondents. The sampling technique used total sampling. All respondents were given Jasa Tami's booklet media "Healthy Adolescents Without Anemia". Univariate analysis used frequency distribution to determine the characteristics of respondents, while bivariate analysis in order to determine the influence between two variables used the Wilcoxon test. Results: The results of statistical tests showed that there is a significant difference about knowledge of health education before and after using booklet media. Before the intervention, the average score of knowledge about anemia was 9.87 and then increased to 12.96 in the post-test. While the average score of the attitude pretest was 44.03 and the average score of the post-test increased by 47.87. Conclusion: there is an influence of health education using Jasa Tami (Healthy Adolescents Without Anemia) booklet media on the knowledge and attitudes of anemia prevention for adolescent girls of Mizalnun 'Ulum Sanrobone Islamic Boarding School in 2023 with the results of the Wilxocon test on the knowledge variable got 0.000 and on the attitude variable obtained a p-value score 0.033.